SURGICAL APPROACH AND OUTCOMES AFTER HAEMORRHOIDECTOMY - Konstantin Kostov (Peytchinski Publishing, 2022)
Purpose: The present study aims to compare and analyze the results of conventional and stapled haemorrhoectomy in patients with haemorrhoidal disease undergoing operative treatment in UMHATEM "N.I.Pirogov" and to determine the accurate surgical approach. Material and Methods: 207 patients with the haemorrhoidal disease (3rd and 4th degree) were operated on for a period of one year from 1.1.2015 to 31.12.2015 in the Department of General, Visceral and Emergency surgery of the University Hospital "Pirogov". In 106 of these stapled haemorrhoidectomy was performed, with the remaining 101- conventional haemorrhoidectomy was performed. Out of the haemorrhoidectomy with a stapler (group S), women were 49 (46.23%), men 57 (53.77%). In the conventional surgery (group C), women were 41 (40.59%), men 60 (59.41%). The age in this retrospective analysis varied from 18 to 81 (average 46 years). Results: From group S there was no post-operative pain reported in 32 (30.19%) patients, 64 (60.38%) complained of moderate pain and 10 (9.43%) of significant pain. From Group C 21 (20.79%) had no post-operative pain, 54 (53.47%) complained of moderate pain and 26 (25.74%) of significant pain. Regarding postoperative haemorrhage from group S, it was minimal to absent in 85.85% (91 patients) of the cases and significant in 15 patients (14.15%). From group C, 68 patients (67.33%) had minimal to absent haemorrhage and 33(32.67%) with significant haemorrhage. Group S morbidity was 9.43% - 10 patients (indication for prolapse, fissure and 2 cases of anal stenosis due to improper manipulation with the stapler). From group C the incidence was 14 patients (13.86%). There were no deaths in both groups-mortality-0%. Conclusion: Compared to literature data, analyzed results indicate that stapled hemorrhoidectomy is the optimal surgical approach to reduce postoperative pain and early recovery to normal activity.